BIOLOGY STUDY PROGRAM SCHOOL OF LIFE SCIENCE AND TECHNOLOGY - NATHANAEL (NIM : 10614069), AQUILA
In the vegetation succession in order to restore the post-disturbance ecosystem, one of many things that influences the presence of a plant species is environmental factors. The influence of several environmental factors to the presence of a plant species is not simple. This study aims to determine the effect of complex environmental factors to the distribution of plant species on post-fire land in 2015 on Mount Papandayan, Garut, West Java using multivariate statistical analysis. Vegetation data was sampled in five different sites with each site containing 3 nested plots which 10x10m plots were use for trees sampling; 5x5m plots for shrubs; and 2x2m plots for herbs. Environmental factor such as height and slope of the land, soil moisture, soil pH, and soil organic N and C content were collected in each plot. Then, multivariate statistic ordination, Canonical Correspondence Analysis (CCA), is carried out to see the effect of several environmental factors on the distribution of plant species on each site. Four species for trees, nine for shrubs, and 23 for herbs were found in this study. Through CCA analysis, it is known that the environmental factors that most influence the distribution of plant species in the research area were soil moisture and land height. There were variations of interaction between environmental factors and plant species distribution in research area where the height of the land positively affected the presence of Metabolos rugosus, the slope affected the presence of Myrsine affinis, while Plantago major spread, Alternanthera philoxeroides, Juncus prismatocarpus, Fimbristylis sp., Ranunculus javanicus, and Angiopteris evecta were positively influenced by soil moisture, soil pH, and soil organic N and C content.